An Android-Based Rabbit Gastrointestinal Disease Diagnosis Expert System Utilizing Forward Chaining Method - Alfaritzi, Difa (JISA(Jurnal Informatika dan Sains), 2022)
Rabbits are animals prone to diseases, mainly affected by digestive system conditions. According to the author's experience, the interviews with rabbit breeders and veterinarians were located in Tangerang, if disorders in the digestive system do not receive proper treatment and will quickly result in death for the rabbit. Rabbit owners sometimes don't know what to do. Obstacles often encountered are limited time, costs, and the number of veterinarians who are still small so that they cannot handle the rabbit immediately. Based on the above problems, it is necessary to design an expert system application with an Android base. The purpose of creating a system is to diagnose diseases in the digestion of rabbits, accompanied by a solution. The method used is to use the forward chaining method to design a digestive disease diagnosis system. This study resulted in the design of an application based on android to diagnose diseases in the digestion of rabbits.